New trends of urban development in Russia in The 18th century - Zolotareva, Milena (Journal of Architecture and Urbanism, 2017)
Architectural and urban planning activity has always been the most important component of the social and political life of any country and has always been subject to regulation. However, the nature, scope and organization of this regulation were different and depended on many factors. Russia was no exception in this respect. Since the Petrine time, the control system and regulation of architectural and construction process have constantly become more complex. In the Petrine era, the urban planning activities were involved in the orbit of government reforms. The primary targets were to change the principles of construction of urban society, to introduce the principles of regularity in all spheres of the public life, to form the regulatory structures of architectural and construction processes. Urban planning process in civil construction was one of the central areas of focus of the Russian urban development policy within the period of the late 17th century – the first half of the 18th century. The first half of the 18th century was marked by a significant step from the city of the Middle Ages towards the Modern Age city including all its elements, such as social and economic, organizational and political, urban planning, architectural and artistic.